1993
DOI: 10.1002/ijc.2910540219
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of MDR‐1 expression by a H‐ras oncogene in a human colon carcinoma cell line

Abstract: In an established colon differentiation model, introduction of a c-H-ras-1 oncogene into a poorly differentiated human colon carcinoma cell line (Clone A) results in changes associated with the acquisition of a more differentiated phenotype. Down-regulation of mdr-1 mRNA was shown to accompany ras-related differentiation events resulting in decreased Pgp synthesis and a significant reduction in membrane Pgp as detected by immunoprecipitation, Western-blot and FACS analysis. Consistent with these observations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…The introduction of a c-H-ras-1 oncogene into a poorly differentiated human colon carcinoma cells has been reported to result in significant reduction of ABCB1 mRNA expression and P-glycoprotein-mediated drug resistance in association with acquisition of a more differentiated phenotype. 13) This suggested that the change in the expression profile of ABC transporters might be related to the properties of the tumors in each differentiation stage. One possible function of ABCA5 in tumors would be as a drug efflux transporter, which might result in multi-drug resistance, in association with ABCB1.…”
Section: Fig 1 Tissue Distributions Of Mrna Expression Of Human Abcmentioning
confidence: 99%
“…The introduction of a c-H-ras-1 oncogene into a poorly differentiated human colon carcinoma cells has been reported to result in significant reduction of ABCB1 mRNA expression and P-glycoprotein-mediated drug resistance in association with acquisition of a more differentiated phenotype. 13) This suggested that the change in the expression profile of ABC transporters might be related to the properties of the tumors in each differentiation stage. One possible function of ABCA5 in tumors would be as a drug efflux transporter, which might result in multi-drug resistance, in association with ABCB1.…”
Section: Fig 1 Tissue Distributions Of Mrna Expression Of Human Abcmentioning
confidence: 99%
“…Growing multicellular prostate tumor spheroids develop quiescent cell subpopulations in central regions with features of intrinsic multicell-mediated drug resistance (117,118). MDR is a constitutional property of differentiated hepatocytes (70) and epithelial cells (54,91). Expression of P-glycoprotein is positively correlated with differentiation in tumor cells (10,48,54,91).…”
Section: Acquired Cell Cycle Properties Of Mdr Cellsmentioning
confidence: 99%
“…MDR is a constitutional property of differentiated hepatocytes (70) and epithelial cells (54,91). Expression of P-glycoprotein is positively correlated with differentiation in tumor cells (10,48,54,91). Reduced growth rate and decreased tumorigenicity correlate with a high level of MDR in many cell lines (8).…”
Section: Acquired Cell Cycle Properties Of Mdr Cellsmentioning
confidence: 99%
“…Therefore, it is possible that oncogenic Ras could up-regulate mdr1b gene expression. However, others have suggested that an oncogenic Ras transformation had no effect on mdr-1 gene expression [9] and H-Ras expression led to the downregulation of mdr-1 gene expression in human colon carcinoma and acute myeloid leukemia cells [10,11]. In this study, we tries to determine the relationship between dominant active H-Ras and mdr1b expression.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have reported that active Ras causes MDR1 expression and leads to anticancer drug resistance [6][7][8]. However, others have found that Ras activation was not able to up-regulate the Jun S et al MDR1 gene [9], and that oncogenic Ras overexpression resulted in the downregulation of MDR1 expression and a subsequent reduction in surface-localized Pgp [10,11].…”
Section: Introductionmentioning
confidence: 99%